2004
DOI: 10.1021/nl049126a
|View full text |Cite
|
Sign up to set email alerts
|

Photoacoustic Tomography of a Nanoshell Contrast Agent in the in Vivo Rat Brain

Abstract: This study demonstrates the feasibility of using nanoshells in vivo as a new contrast-enhancing agent for photoacoustic tomography. Deep penetrating near-infrared light was employed to image the in vivo distribution of poly(ethylene glycol)-coated nanoshells circulating in the vasculature of a rat brain. The images, captured after three sequential administrations of nanoshells, present a gradual enhancement of the optical absorption in the brain vessels by up to 63%. Subsequent clearance of the nanoshells from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
343
0
3

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 442 publications
(350 citation statements)
references
References 16 publications
4
343
0
3
Order By: Relevance
“…S3). It has been demon- strated that a variety of gold nanocolloids are already entering in vivo clinical trials (19,(29)(30)(31)(32)(33). Among them, Au nanorods present particularly good optical absorption in the near-infrared region, tunable by changing the aspect ratio.…”
Section: B and Dmentioning
confidence: 99%
See 2 more Smart Citations
“…S3). It has been demon- strated that a variety of gold nanocolloids are already entering in vivo clinical trials (19,(29)(30)(31)(32)(33). Among them, Au nanorods present particularly good optical absorption in the near-infrared region, tunable by changing the aspect ratio.…”
Section: B and Dmentioning
confidence: 99%
“…It has been shown that PAT can depict subsurface tissue structures and functional changes noninvasively with resolution up to 100 m (14, 15). Like other optical modalities, PAT is highly sensitive in mapping and quantifying the dynamic distribution of optical contrast agents such as metallic nanocolloids and organic dyes (16)(17)(18)(19)27).In the present work, we have fabricated a composite-material nanoparticle, which we call ''nanowonton.'' The nanowonton has a Co core and an Au thin-film coating and is a construct similar to the Chinese eatable called the wonton (see Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Due to their unique physicochemical properties, gold nanorods (Au-NRs) are being increasingly utilized in consumer and medical applications, including photothermal therapy, bioimaging, drug delivery, and site specific catalysis [1][2][3]. Specifically, these distinctive nanogold parameters include a general biocompatibility, plasmonic properties, enhanced surface reactivity, and ease of functionalization [4].…”
Section: Introductionmentioning
confidence: 99%
“…Some of those commonly used for PAT include spherical gold NPs [304, 314 -320] , nanorods [321 -327] , nanostars [328] , nanocages [305, 329 -334] , hollow nanoshells [335] , and composite materials with gold nanoshells: SiO 2 @Au, [306,336,337] Fe 3 O 4 @Au, [314] cobalt@gold NPs, [110] gold-speckled silica [316,320] , and gold nanobeacons [338,339] . The reasons for such an attention to gold nanosystems are many fold: they have tunable size-and shape-dependent plasmonic properties [340,341] , which allow them to absorb and scatter light from the visible to NIR region and make them suitable for image-guided therapy [325, 342 -344] and PTA of tumors [345 -347] .…”
Section: Gold-based Nanomaterialsmentioning
confidence: 99%